2018
DOI: 10.1534/genetics.118.301110
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impact of the H2A.Z Histone Variant During Meiosis in Saccharomyces cerevisiae

Abstract: Among the collection of chromatin modifications that influence its function and structure, the substitution of canonical histones by the so-called histone variants is one of the most prominent actions. Since crucial meiotic transactions are modulated by chromatin, here we investigate the functional contribution of the H2A.Z histone variant during both unperturbed meiosis and upon challenging conditions where the meiotic recombination checkpoint is triggered in budding yeast by the absence of the synaptonemal c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 81 publications
8
12
0
Order By: Relevance
“…Contrary to current understanding, we find that the Pch2-Hop1 module is crucial for checkpoint function in response to both recombination and synapsis defects, thus revealing a shared meiotic checkpoint cascade. Meiotic checkpoint responses are transduced by DNA break-dependent phosphorylation of Hop1 [7, 8]. Based on our data and on the effect of Pch2 on HORMA topology [9–11], we propose that Pch2 promotes checkpoint proficiency by catalyzing the availability of signaling-competent Hop1.…”
mentioning
confidence: 78%
“…Contrary to current understanding, we find that the Pch2-Hop1 module is crucial for checkpoint function in response to both recombination and synapsis defects, thus revealing a shared meiotic checkpoint cascade. Meiotic checkpoint responses are transduced by DNA break-dependent phosphorylation of Hop1 [7, 8]. Based on our data and on the effect of Pch2 on HORMA topology [9–11], we propose that Pch2 promotes checkpoint proficiency by catalyzing the availability of signaling-competent Hop1.…”
mentioning
confidence: 78%
“…H2A.Z is lost (Gonzalez-Arranz et al, 2018), but H2A.Z foci persisted in the absence of the SWR1 complex, as seen in enhanced images (Figures 1B,C). Double staining with Zip1 antibodies, as a marker of synapsed chromosomes, showed that these SWR1-independent H2A.Z foci were primarily located at chromosome ends ( Figure 1B); 65.4% of the swr1 spread pachytene nuclei scored (n = 26) displayed H2A.Z at telomeres.…”
Section: H2az Remains At Chromosome Ends In the Absence Of Swr1mentioning
confidence: 78%
“…Our previous cytological studies have shown that H2A.Z extensively decorates meiotic chromatin in wild-type pachytene chromosomes, except in the ribosomal DNA (rDNA) region where its presence is markedly reduced (Gonzalez-Arranz et al, 2018). In the swr1 mutant, the bulk of chromatin-associated FIGURE 1 | H2A.Z localizes to chromosome ends during meiotic prophase I.…”
Section: H2az Remains At Chromosome Ends In the Absence Of Swr1mentioning
confidence: 97%
See 2 more Smart Citations